EFL students' views, experiences, and expectations toward plagiarism practices in Indonesian higher education - Surahmat Agus Munandar; Sahril Nur; Andi Asrifan; Hussain Hameed Mayuuf; Andi Anto Patak (Center for Humanities and Innovation Studies, 2023)
This research investigates the English as a Foreign Language (EFL) students' views, experiences, and expectations toward plagiarism practices in Indonesian higher education. The researchers employed a qualitative method with a case study approach. Ten EFL students conveniently participated in this study. The data were obtained through semi-structured interviews. The data was analyzed using thematic analysis. This study showed that EFL students view plagiarism as an act of taking someone's idea, a bad habit, intentional and unintentional. EFL students' experience with plagiarism revealed that they committed plagiarism due to a lack of understanding and unfamiliarity with the plagiarism concept. Besides, the students reported being too lazy and less likely to read. EFL students expect to reduce plagiarism by being more active in reading and providing free workshop seminars, and lecturers must strictly apply the rules. Moreover, instilling self-motivation, receiving advice and feedback from the lecturer, understanding the definition of plagiarism, having the desire to read, enhancing personal awareness, doing Turnitin checker, using an application, and self-confidence were their expectations of reducing plagiarism practices.